Academic Emergency in the South Cone: The Social Scientists Relocalization Program (1973-1975) - Bayle, Paola (2008)
This article tries to reconstruct the strategies carried out by the Latin-American Council of Social Sciences (CLACSO), in joint with a set of institutions of the region, to re-locate to social scientists after the military coups that began with Chile, in the year 1973. In this work we hold that CLACSO could realize this task thanks to the relations of resources that it began, from its creation, with academic and philanthropic institutions of different countries of the world. In agreement with the approaches that were coming developing from the previous decade among the social Latin-American scientists - in relation with the autonomy of the research centers and the brain drain towards industrialized countries - this politics of relocation adds light on a set of key moments of the process of institutionalization and disinstitutionalization of the social sciences in the South Cone in Latin-America.